The advantages of microflow LC–MS/MS compared with conventional HPLC–MS/MS for the analysis of methotrexate from human plasma. (June 2013) - Christianson, Chad C; Johnson, Casey JL; Needham, Shane R
Background: In support of bioanalysis, there has always been a desire to improve detection limits and reduce scale. Microflow LC (MFLC) coupled with MS accomplishes both of these goals.Results: As such, MFLC coupled with an MS system was used to generate bioanalytical validation data that met US FDA criteria. The MFLC–MS/MS data was compared with the same method with the use of conventional HPLC–MS/MS and a more than 14× S/N improvement was found with the MFLC–MS/MS method. Methotrexate was used as a model molecule to demonstrate the validation of the method from human plasma. The MFLC–MS/MS method was demonstrated to be accurate (±7%) and precise (12.9% at the LLOQ and a maximum of 11.6% at all other concentrations) across the dynamic range of the assay (1–1000 ng/ml) and compared well with the HPLC–MS/MS method. The MFLC bioanalytical validation was performed at a flow rate of 35 µl/min on a 0.5-mm inner diameter (I.D.) column, whereas, for the same linear velocities on the 2.0-mm I.D. column, the conventional HPLC bioanalytical validation was performed at 700 µl/min. Since the flow rate of the MFLC system is 20-times less than the HPLC system, the consumable solvent and disposal cost to perform the MFLC validation was significantly less.Conclusion: MFLC–MS/MS can be used to perform bioanalytical method validations with increased MS signal, reduced source contamination and reduced solvent consumption.